FRI0058 14-3-3 eta marks radiographic progression in an early arthritis cohort. (23rd January 2014) - Britsemmer, K.; Marotta, A.; Maksymowych, W. P.; van Schaardenburg, D.
Abstract : Background: Diagnosis of RA in its early stages enables the initiation of appropriate therapies that can alter the disease course and improve patient outcomes. ACPAs are useful for RA diagnosis and prognosis, yet a subset of patients are sero-negative in early disease and many remain so, even with established disease. It is recognized that current clinical/serological measures account for only 32% of the total variance in predicting joint damage. 1 Therefore, there is a need for new complementary diagnostic markers that can assist clinicians in better identifying higher risk patients. 14-3-3eta is a soluble diagnostic RA marker involved in the pathophysiology of the disease and marks joint damage in both RA and PsA. Objectives: We investigated whether 14-3-3eta plasma expression marks joint damage progression in ACPA+ve and ACPA-ve RA patients. Methods: Baseline (BL) and Year 1 14-3-3eta levels were quantified in 62 early RA patients using banked plasma samples from the Reade cohort. 38 (61%) were ACPA+ve and 24 (39%) ACPA-ve. Mean age was 54 years, 79% were female, median duration of symptoms was 4 months (IQR 3-7) and patients were DMARD naïve at baseline. Joint damage progression from BL to Year 5 according to a ΔSHS of >0.5 was categorized as progression "1" and ΔSHS≤0.5 as no progression "0". Multivariate regression analyses were performed to determine which variables predicted joint damage progression with the probability (p) for a variable to enter the model p<0.25 and to leave being p>0.1. Those assessed were RF-IgM titres, CRP, ESR, TJC28 and SJC28 as well as baseline and Year 1 14-3-3eta titres and positivity (cut-off of 0.19ng/ml). Results: 38 of the 62 patients (61%) were +ve for 14-3-3eta; 33 of the 38 ACPA+ve patients (87%) as well as 5 of the 24 ACPA-ve (21%) were 14-3-3eta+ve. This, taken together with the Pearson correlation between ACPA and BL 14-3-3eta titres being r=0.076 (p=0.61), agrees with earlier reports of 14-3-3eta being independent of and complementary to ACPA. 2 In the ACPA+ve group, 18 of the 38 (47%) patients progressed at year 5. Mean (SD) and median (range) SHS scores at year 5 were 16.8 (29.0) and 2.0 (0.0-145). Independent predictors of joint damage progression that emerged from the analysis were BL 14-3-3eta (Chi-Sq 4.2, p=0.04), CRP (Chi-Sq 12.0, p<0.001), ESR (Chi-Sq 8.5, p<0.004), and TJC28 (Chi-Sq 5.1, p=0.02). The R 2 for the combination of these variables with and without 14-3-3eta were 0.52 and 0.39, respectively. Importantly, in the ACPA-ve group, 13 of 24 (54%) progressed and had mean (SD) and median (range) SHS scores at year 5 of 9.7 (23.4) and 2.0 (0.0-108). Of all the clinical/serological measures assessed in the regression analysis, in the ACPA-ve group only BL 14-3-3eta positivity (Chi-Sq 7.8, p=0.005) and BL 14-3-3eta titres (Chi-Sq 6.5, p=0.01) were independent predictors of joint damage progression, together delivering an R 2 of 0.49. Conclusions: Plasma 14-3-3eta is a complementary marker to ACPA in early RA. In ACPA+ves, 14-3-3eta as well as ESR, CRP and TJC independently predict joint damage progression; while in ACPA-ves, the only predictor was 14-3-3eta. This novel marker should be further examined for clinical insights into early RA diagnosis and patient management, in both ACPA+ves and -ves. References: de Rooy DPC et al. Rheum. 2011. 50:93. 2) Marotta A et al. Arthritis Rheum. 2011.63 Suppl 10:378. Disclosure of Interest: K. Britsemmer: None Declared, A. Marotta Employee of: Augurex Life Sciences Corp, W. P. Maksymowych: None Declared, D. van Schaardenburg: None Declared